2021
DOI: 10.1155/2021/9949777
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review with Meta-Analysis: Effectiveness and Safety of Acupuncture as Adjuvant Therapy for Side Effects Management in Drug Therapy-Receiving Breast Cancer Patients

Abstract: Objective. To investigate the potential benefits and safety of acupuncture on managing side effects induced by drug therapies in patients with breast cancer using a PRISMA standard systematic review and meta-analysis. Methods. Published randomised controlled trials from nine databases in English and Chinese language were searched. Trials with a real acupuncture treatment group and a control group with sham acupuncture, no treatment, or waitlist control were included. The primary outcome of this study was the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…1). 1‐134 Of those, 65 of 94 publications (69.1%) were included in the qualitative analysis because they reported at least 1 type of AE,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1). 1‐134 Of those, 65 of 94 publications (69.1%) were included in the qualitative analysis because they reported at least 1 type of AE,…”
Section: Resultsmentioning
confidence: 99%
“…Some meta-analyses that focus on the effectiveness of acupuncture for treating symptoms in patients with breast cancer or pain in oncological patients do report AEs and conclude that acupuncture is a safe intervention. 25,31,32 A prospective, observational study on nononcological patients by Witt et al in 2009 indicated that acupuncture was a relatively safe treatment option 14 : common adverse effects were bleeding These were crossover trials that had insufficient reporting for inclusion in the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Effectiveness and safety of acupuncture in the management of gastrointestinal disorder, neuropathy, arthralgia, joint symptoms, and cognitive impairment as side effects in breast cancer patients was recently showed by Chan and colleagues' meta-analysis [30].…”
Section: Discussionmentioning
confidence: 97%